2020
DOI: 10.1016/j.isci.2020.101639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Measures on Short-Term Electricity Consumption in the Most Affected EU Countries and USA States

Abstract: As COVID-19 spreads worldwide, governments have been implementing a wide range of measures to contain it, from movement restrictions to economy-wide shutdowns. Understanding their impacts is essential to support better policies for countries still experiencing outbreaks or in case of emergence of subsequent pandemic waves. Here we show that the cumulative decline in electricity consumption within the five months following the stay-home orders ranges between 3-12% in the most affected EU countries and USA state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 14 publications
1
37
0
Order By: Relevance
“…In particular, the most severe restrictions put in place in April led the CSS down by 11.3 €/MWh, turning profits into an average loss of 4.15 €/MWh. The present study extends the findings of previous works (Abadie, 2020;López Prol and O, 2020;Santiago et al, 2021) by adding to the energy demand also an analysis of the trend the electricity price, which in Spain is subject to a daily market-based competition (Ciucci, 2020). This makes it possible to get a first estimate of the revenue lost by the Spanish electricity sector during the lockdown.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…In particular, the most severe restrictions put in place in April led the CSS down by 11.3 €/MWh, turning profits into an average loss of 4.15 €/MWh. The present study extends the findings of previous works (Abadie, 2020;López Prol and O, 2020;Santiago et al, 2021) by adding to the energy demand also an analysis of the trend the electricity price, which in Spain is subject to a daily market-based competition (Ciucci, 2020). This makes it possible to get a first estimate of the revenue lost by the Spanish electricity sector during the lockdown.…”
Section: Introductionsupporting
confidence: 78%
“…This drop changed also the energy mix, with a larger share from renewables and a subsequent reduction in CO2 emissions. A more recent analysis made use of dynamic harmonic regression to compare expected and actual electricity consumption data from March to July 2020 in Spain, other EU countries and the USA (López Prol and O, 2020). The authors found, for Spain, an energy demand during the lockdown 21% lower than forecasted, which reached the baseline levels by the end of July.…”
Section: Introductionmentioning
confidence: 99%
“…One strand of literature focuses on the implications of these measures for energy demand (cf. Graf et al [14], Prol and Sungmin [15]). Graf et al [14] highlight that the Covid-19 lockdown has reduced the net demand, while controllable generation units had to react to this demand shock.…”
Section: Existing Literature Analyzing the Impact Of The Covid-19 Crimentioning
confidence: 98%
“…In their analysis, they focus on the Italian electricity market with decreasing day-ahead prices and increasing costs for re-dispatch measurements. Prol and Sungmin [15] focus on the first wave in Europe and the USA during the spring 2020 and argue that most countries have recovered baseline demand levels by the end of July. Cicala [16] argues in the same way and finds that working from home (home office) in the United States has led to an increase in residential electricity consumption.…”
Section: Existing Literature Analyzing the Impact Of The Covid-19 Crimentioning
confidence: 99%
“…Previous studies have revealed electricity demand or consumption scenarios in developed economies. For instance, the cumulative decrease in electricity consumption in the EU countries and the states of the USA was between 3% and 12%, respectively, following the stay-home orders for five months ( Prol and O, 2020 ). However, a recent review found that “ fully enforced lockdowns and stay home orders have increased the residential sector energy demand by a range from 11% to 32% for several countries ” ( Krarti and Aldubyan, 2021 ).…”
Section: Introductionmentioning
confidence: 99%